Current techniques for the treatment of spasticity and their effectiveness - Hong-Xiao Li; Ke Xu; Shan-Lin Chen; Shu-Feng Wang; Wen-Jun Li (EFORT Open Reviews)
This review highlights the role of existing spasticity treatment methods in reducing muscle tone and improving function. The surgical methods today mainly include selective dorsal rhizotomy, selective neurotomy, intrathecal baclofen treatment (ITB), etc. These techniques (except ITB) can lower patients’ muscular tone in the long term and improve function to some extent. The young procedures, contralateral C7 nerve transfer and T1 neurotomy, are still under research. ITB and nonsurgical treatment methods, botulinum toxin A (BoNT-A) and extracorporeal shockwave therapy (ESWT), can reduce muscle tone in the short term, but the long-term efficacy is unsatisfactory. In addition, the effects of improving function are relatively controversial. The economic cost of these treatment methods is also heavy for patients. In addition, some studies have reported that some kinds of electrical/magnetic stimulation can improve the patients’ function. They can potentially be used as an adjunctive treatment for spasticity. According to current studies and our own experience, surgery methods (except ITB) are still recommended for patients, whose spasticity has a major detrimental influence on their everyday lives, taking into account patient benefits and cost-effectiveness. There are also some problems in the current research on spasticity treatment, such as incomplete guidelines and a relative lack of high-quality studies, which is what the doctors need to strive for. Further exploration is needed to find the treatment methods that can reduce muscle tone while improving patients’ function to better benefit patients.